Implementation of the Land Swap Agreement (Ruislag) for Waqf Land for the Construction of a Toll Road - Umi Masnur Adniyah (Justisi)
This study aims to determine the process of implementing land swap agreements for waqf land used for toll road construction and to analyze the government's responsibilities in the implementation of the swap.